STRATEGI PENGEMBANGAN WISATA AIR PANAS SIPATN LOTUP OLEH DINAS PEMUDA OLAHRAGA DAN PARIWISATA KABUPATEN SANGGAU - Aprila, Agnes; Isdairi, Isdairi; Sulisdian, Indah (PublikA Jurnal Ilmu Administrasi Negara (e-Journal), 2023)
This study aimed to analyze the strategy execution of Sipatn Lotup Hot Water tourism development which was done by the Youth, Sport and Tourism Department of Sanggau Regency. This study used a qualitative research method with a descriptive-analytical research design. This study used Brysonâ€™s strategy planning theory (2016:55) which consisted of resources condition, strategic planning, community participation, and promotion. The results showed that the condition of the Youth, Sport and Tourism Department of Sanggau resources were still a weakness due to the lack of human, financial, and information resources so that it became an obstacle to the development of Sipatn Lotup Tourist Attractions and the strategic planning that had been carried out was supported by the existence of Regional Long-Term Development Plan targets for the tourism sector and the formulation of more detailed planning documents such as the Master plan which could be a strength for the Sipatn Lotup Tourist Attractions development process. The results also showed that there was a lack of local community participation because they thought that the tourism sector was still not promising to be held in the area and the promotion efforts were not yet optimal.Â Keywords: Strategy, Development, Tourism.